2011
DOI: 10.1007/s00276-011-0830-x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular ossicle in interphalangeal joint of the great toe and clinical implication

Abstract: Failure of closed reduction for an interphalangeal joint dislocation of the great toe resulted from an intra-articular ossicle interposed between the articular cartilages of the phalanges. The knowledge concerning the intra-articular ossicle is unclear. A study was thus carried out on 100 fresh great toes to document the appearance, number, size, and location of the intra-articular ossicle found in the interphalangeal joint of the great toe. Roentgenographic studies of the joint revealed 86% of bony mass repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…The anatomy of the joint makes closed reduction difficult to achieve [ 15 ]. Suwannahoy et al [ 16 ] conducted a cadaveric study on 100 fresh great toes to document the appearance, number, size, and location of an intra-articular ossicle found in the IP joint space of the great toe. Radiographic studies of the joint revealed 86% of bony mass representing either the sesamoid bone or an intra-articular ossicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the joint makes closed reduction difficult to achieve [ 15 ]. Suwannahoy et al [ 16 ] conducted a cadaveric study on 100 fresh great toes to document the appearance, number, size, and location of an intra-articular ossicle found in the IP joint space of the great toe. Radiographic studies of the joint revealed 86% of bony mass representing either the sesamoid bone or an intra-articular ossicle.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the bony mass was found on the dorsal surface of the plantar capsule of the IP joint 88% of the time. The challenge in closed reduction is likely to be a result of the interposed plantar capsule with the sesamoid as can be deduced from the work of Suwannahoy et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ovoid ossicle seen at the inter‐phalangeal joint of digit 1 in all animals suggests that the ossicle is a normal anatomical finding in this species. It is most likely that the ossicle is intra‐articular as described for the great toe in humans (Suwannahoy et al., ) and should be differentiated from an avulsion fracture or intra‐articular mineralized body.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually single and bilateral (Roukis and Hurless, 1996) although the presence of double ossicles has also been reported (Davies et al, 2003;Suwannahoy et al, 2012). In humans, they can be located plantarmedial, plantarlateral or plantar to the inter-phalangeal joint of the hallux and their shape varies from spherical, oval, elliptical, rectangular or triangular (Roukins and Hurless, 1996).…”
Section: Discussionmentioning
confidence: 99%